The role of hypoxic signalling in metastasis: towards translating knowledge of basic biology into novel anti-tumour strategies - Araos, Joaquín; Sleeman, Jonathan P.; Garvalov, Boyan K. (Clinical & experimental metastasis, 2018)
Hypoxia is a characteristic feature of many cancer types, which ensues when the growth of a tumour outpaces its oxygen supply. The cellular response to reduced oxygen tension is centred around the hypoxia-inducible transcription factors (HIFs), which become stabilized under hypoxic conditions. In addition, a number of oxygen-independent mechanisms of HIF regulation have been described, which also play a role at distinct stages of tumour progression. Hypoxia and HIF activity have been linked to the control of all hallmarks of cancer, and increased levels of hypoxia or HIFs in human tumours are typically associated with poor prognosis. In this review, we describe the current knowledge about the role of hypoxic signalling in tumour metastasis, which is the main cause of cancer-related mortality. The members of the HIF family, HIF1α, HIF2α and HIF3α, play important functions at all key stages of metastatic dissemination. This includes local migration within the tumour and invasion of the surrounding stromal tissue through induction of an epithelial-mesenchymal transition (EMT)-like process, remodelling of the extracellular matrix, intravasation and extravasation, survival and dissemination through the circulation, generation of premetastatic niches to support secondary tumour growth, colonisation of distant sites, and tumour cell dormancy. The central role of hypoxic signalling in tumour growth and metastasis, as well as its involvement in therapy resistance, have motivated efforts to monitor tumour hypoxia through various invasive and non-invasive techniques, and to identify inhibitors of HIFs, their regulators or their targets. Recent progress in these areas has provided indications that such approaches may represent a viable strategy for translating basic knowledge about tumour hypoxia and HIF biology into novel therapeutic strategies for metastatic cancer.